2022
DOI: 10.3389/fpubh.2022.903547
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin D supplementation on the incidence and prognosis of depression: An updated meta-analysis based on randomized controlled trials

Abstract: BackgroundThere have been several controversies about the correlation between vitamin D and depression. This study aimed to investigate the relationship between vitamin D supplementation and the incidence and prognosis of depression and to analyze the latent effects of subgroups including population and supplement strategy.MethodsA systematic search for articles before July 2021 in databases (PubMed, EMBASE, Web of Science, and the Cochrane Library) was conducted to investigate the effect of vitamin D suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The role of vitamin D is generally indicated as protective [ 37 ] by potential reducing of the negative effects of dopaminergic toxins, possibly by increasing glial cell-line-derived neurotrophic factor and affecting serotonin transmission in the brain, linking dopaminergic and serotonergic systems [ 44 , 45 ]. Similarly, the preventive role of vitamin D is confirmed by the recent meta-analysis of RCTs by Xie et al [ 46 ], which indicated its beneficial impact on the incidence of depression.…”
Section: Discussionmentioning
confidence: 79%
“…The role of vitamin D is generally indicated as protective [ 37 ] by potential reducing of the negative effects of dopaminergic toxins, possibly by increasing glial cell-line-derived neurotrophic factor and affecting serotonin transmission in the brain, linking dopaminergic and serotonergic systems [ 44 , 45 ]. Similarly, the preventive role of vitamin D is confirmed by the recent meta-analysis of RCTs by Xie et al [ 46 ], which indicated its beneficial impact on the incidence of depression.…”
Section: Discussionmentioning
confidence: 79%
“…A comprehensive meta-analysis conducted by Xie et al in 2022 [123] provides valuable insights into this matter. The findings consistently highlight the relevance of serum 25(OH)D levels, dosage of vitamin D supplementation, body mass index (BMI), gender, and intervention duration.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of 29 RCTs with 4504 participants concluded that vitamin D supplementation reduced MDD incidence (standardized mean difference: −0.23) and improved responses to the treatment of depression (standardized mean difference: −0.92) [154]. The effects of 2800 IU/d vitamin D over >8 weeks were significant for both prevention and treatment.…”
Section: Major Depressive Disordermentioning
confidence: 99%